1984
DOI: 10.1139/v84-257
|View full text |Cite
|
Sign up to set email alerts
|

Examination of the molecular properties of D-fructose and L-sorbose by abinitio LCAO-MO calculations

Abstract: Abinitio SCF LCAO-MO calculations at the STO-3G level have been performed on β-D-fructopyranose (1) and α-L-sorbopyranose (2) using crystallographic data as the geometrical input. Molecular properties of 1 and 2 are discussed in terms of orbital energies, total energy, ionization potentials, Mulliken population analysis, and electrostatic potentials, with a particular emphasis on the possible consequences of these features as regards the sweet taste of these two ketoses. No correlation was found, for example, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
4
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 7 publications
1
4
0
Order By: Relevance
“…This approach seems to lend support to Birch's proposal since it was found that the zone of greatest hydrophilicity in P-D-fructopyranose was centered around the 4-OH group, thus possibly making this group essential for sweetness. This is also consistent with our prediction that the 0 -4 atom would be the most attractive site for protonation (9). Of relevance are also the observations that both the 6-thio-(15) and the 6-carba-(16) analogs of P-Dfructopyranose are intensely sweet, presumably as a result of the expansion of the hydrophobic region of the molecule (2).…”
supporting
confidence: 90%
“…This approach seems to lend support to Birch's proposal since it was found that the zone of greatest hydrophilicity in P-D-fructopyranose was centered around the 4-OH group, thus possibly making this group essential for sweetness. This is also consistent with our prediction that the 0 -4 atom would be the most attractive site for protonation (9). Of relevance are also the observations that both the 6-thio-(15) and the 6-carba-(16) analogs of P-Dfructopyranose are intensely sweet, presumably as a result of the expansion of the hydrophobic region of the molecule (2).…”
supporting
confidence: 90%
“…The simplest carbohydrates are monosaccharides, whose low-energy conformations can be reliably predicted by suitably chosen computational methods . Theoretical conformational studies appeared for glucose, fructose, ribose, , deoxyribose, , and erythrose. The availability of high-accuracy structural and spectroscopic data for gas-phase C 4 and C 5 monosaccharides is a prerequisite for their possible detection in space. …”
Section: Introductionmentioning
confidence: 99%
“…To prevent the sugar's thermal decomposition, 30 the two groups used high-speed laser evaporation which was combined with microwave (MW) spectroscopy to measure rotational In addition to the recent MW spectroscopic search of D-fructose, 7,29 there were (mostly) low-level theoretical studies on this sugar in the gas phase which will now be briefly reviewed. The early ab initio RHF/STO-3G calculations by Szarek et al 31,32 assumed the crystal structure as input geometry. These authors also reported semiempirical AM1 optimized structures and energies of β-D-fructopyranose.…”
Section: Introductionmentioning
confidence: 99%